2018
DOI: 10.1097/iae.0000000000001862
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Aflibercept and Ranibizumab Injections for Type 3 Neovascularization

Abstract: There was no difference between the aflibercept and ranibizumab treatments in terms of visual acuity improvement after 12 months in patients with Type 3 neovascularization. However, geographic atrophy developed more frequently in the aflibercept-treated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
3
12
1
Order By: Relevance
“…Incident MAs after the baseline (time of first diagnosis of neovascular AMD) were detected via colour fundus photography (CFP), SD‐OCT, infrared reflectance imaging and autofluorescence (AF) imaging, in line with our previous investigations (Cho et al 2015; Cho et al 2018; Cho et al 2020). The criteria for the diagnosis of MA were as follows: (i) minimum hypopigmented area of 250 µm within the macular vascular arcades; (ii) increased visibility of the underlying choroidal vessels or uniformly reduced signal on AF images; (iii) confirmation of increased signal transmission in the choroid because of the absence of RPE on the SD‐OCT images.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…Incident MAs after the baseline (time of first diagnosis of neovascular AMD) were detected via colour fundus photography (CFP), SD‐OCT, infrared reflectance imaging and autofluorescence (AF) imaging, in line with our previous investigations (Cho et al 2015; Cho et al 2018; Cho et al 2020). The criteria for the diagnosis of MA were as follows: (i) minimum hypopigmented area of 250 µm within the macular vascular arcades; (ii) increased visibility of the underlying choroidal vessels or uniformly reduced signal on AF images; (iii) confirmation of increased signal transmission in the choroid because of the absence of RPE on the SD‐OCT images.…”
Section: Methodssupporting
confidence: 80%
“…It is well known that the incidence of MA among patients with type 3 NV is significantly higher than that among those with other types of neovascular AMD (Cho et al 2015; Cho et al 2018). Furthermore, the choroidal thickness is lower and SDD is more frequent among patients with type 3 NV than in those with other types of NV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on disease type, 12 months after treatment, the occurrence rates were reported to be 36.6% in the eyes with RAP, 3.8% in the CRA, chorioretinal atrophy progression; logMAR, logarithm of the minimum angle of resolution; CT, choroidal thickness; FRT, foveal retinal thickness; CNV, choroidal neovascularization eyes with AMD other than RAP treated with IVR, and 10.6% treated with IVA [17,18,25]. In another report, the incidence rates of macular atrophy in the eyes with RAP were 19% in the IVR-treated group and 42.9% in the IVA-treated group 12 months after treatment, a difference that reached significance [22]. Several factors such as the frequency of injections, baseline choroidal thickness, and AMD subtype have been reported as risk factors for macular atrophy, but no definitive conclusions have been reached [17,19].…”
Section: Discussionmentioning
confidence: 95%
“…However, it is unclear if anti-VEGF therapy also prevents later development of CRA in high myopia. In addition, although a recent study reported that the incidence of macular atrophy was higher in the eyes with RAP treated with intravitreal injections of aflibercept (IVA) (Eylea, Regeneron Pharmaceuticals, Tarrytown, NY, Bayer AG, Leverkusen, Germany) compared with intravitreal injections of ranibizumab (IVR) (Lucentis, Genentech, South San Francisco, CA) [18,22], it is unclear if the prevalence rates of CRA development after administration of anti-VEGF therapy for mCNV differ between IVA and IVR. The current study compared the progression of CRA between IVA and IVR and investigated the difference between those with and without CRA enlargement.…”
Section: Introductionmentioning
confidence: 99%